Synthesis and evaluation of the anti-bacterial effect of modified silica gel supported silver nanoparticles on E. coli and S. aureus - Belete Tessema; Girma Gonfa; Sintayehu Mekuria Hailegiorgis; Getachew Adam Workneh; Tigist Getachew Tadesse (Results in Chemistry, 2024)
Scientists are looking for new antibacterial agents to disinfect point-of-use water sources due to the dearth of clean drinking water in developing nations and disaster areas. Because of the growth of antibiotic and disinfectant resistance as well as the emergence of multiple unfavorable effects brought on by using current antibacterial agents like chlorine compounds, this is the case. Because of their antibacterial properties, silver nanoparticles (AgNPs) have become a useful replacement for other nanomaterials. This study aimed to evaluate the antibacterial activity of AgNPs embedded in modified silica gel (MSG). It was used to kill Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) and to test its efficacy in water purification in a batch and zone of inhibition system. Trimethyl chlorosilane (TMCS) was used to modify MSG, which was then ground into powder using a process known as the ambient dry method. Using a reagent made from Vernonia amygdalina leaf extract, AgNPs were prepared using a green technique. With the aid of FT-IR, BET, XRD, SEM/EDX, and UV–vis spectrophotometers, the MSG supported by AgNPs was studied. E. coli and S. aureus were tested for their antibacterial abilities in MSG supplements with AgNPs samples. AgNPs have excellent antibacterial properties that enable zone inhibition and batch system tests with MSG. Batch system tests showed that both gram-positive and gram-negative microorganisms decreased effectively after 10 min of exposure. Zone inhibition tests indicated that MSG with AgNPs was effective against both kinds of bacteria.